2020
DOI: 10.1016/j.jhsg.2020.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Local Hematoma Block as Postoperative Analgesia in Pediatric Supracondylar Humerus Fractures

Abstract: Supracondylar humerus fracture (SHF) is the most common type of fracture in children. The aim of this study was to evaluate the efficacy of local hematoma block with 0.25% bupivacaine as postoperative pain control in patients with pediatric SHF who underwent closed reduction pin fixation. Methods: We performed an institutional review boardeapproved, prospective cohort study of 65 patients with SHF treated with closed reduction percutaneous pin fixation. For 6 months, all patients were randomly divided into 2 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The results showed that hematoma block could relieve pain and reduce the dose of postoperative morphine, codeine and other analgesics. In a recent study, Astacio et al [22] performed a 0.25% bupivacaine local hematoma block in children with humeral supracondylar fracture after CRPP. Compared with the control group, postoperative use of morphine doses and pain score were not signi cantly different between groups, therefore the author suggested that hematoma block is not an effective method to relieve postoperative pain of supracondylar humeral fracture [22] .…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that hematoma block could relieve pain and reduce the dose of postoperative morphine, codeine and other analgesics. In a recent study, Astacio et al [22] performed a 0.25% bupivacaine local hematoma block in children with humeral supracondylar fracture after CRPP. Compared with the control group, postoperative use of morphine doses and pain score were not signi cantly different between groups, therefore the author suggested that hematoma block is not an effective method to relieve postoperative pain of supracondylar humeral fracture [22] .…”
Section: Discussionmentioning
confidence: 99%
“…They also noted HB treatment's effect on pain severity as significantly better than PSA's effect. Alternatively, in a prospective cohort study, Astacio et al evaluated the efficacy of local 0.25% bupivacaine HB as postoperative pain control in pediatric patients (average age = 6 years, range 4-11) with supracondylar humeral fracture who underwent closed reduction pin fixation 41. This study's results did not favor the use of HB to improve pain control or decreased opioid use on postoperative day 1.…”
mentioning
confidence: 99%